A 2.1 ppm/°C, 0.55–2.4 V, 5.6 nW, 235 mV, CMOS-only subthreshold voltage reference. (July 2021) - Duan, Quanzhen; Lin, Chenxi; Liu, Peiju; Huang, S.; Meng, Zhen
Abstract: This study presents a high-precision, ultra-low-power, and CMOS-only subthreshold voltage reference. V PTAT with a positive temperature coefficient (TC) and V CTAT with a negative TC were generated to obtain a low-temperature dependence voltage reference. V PTAT was implemented using two standard-threshold voltage (STV) transistors working in the subthreshold region, while, V CTAT was implemented by a high-threshold-voltage (HTV) transistor and an STV transistor biased in the subthreshold region to obtain a ΔV GS with a negative TC. The voltage reference circuit was implemented via a standard 0.18- μ m CMOS process with the core size around 0.022 mm 2 . The pre and post simulation results showed an average output reference voltage of around 235 mV with different supply voltages. Under a temperature range of −30 to 80 °C and the supply voltage of 0.55 V, the best TCs were as low as 2.1 and 7.6 ppm/°C for pre and post simulations, respectively. The total power consumption was only 5.6 nW when the supply voltage is 0.55 V.